A Case of Superficial Femoral Arteriovenous Fistula and Severe Venous Stasis Ulceration, Managed with an Iliac Extender Prosthesis. (20th July 2017) - Ilonzo, Nicole; Goss, Selena; Yang, Chun; Dudkiewicz, Michael
Abstract : Most femoral artery arteriovenous fistulas occur as a result of percutaneous interventions. However, arteriovenous fistulas can occur in the setting of trauma, with resultant consequences such as heart failure, steal syndrome, or venous insufficiency. Indications for endovascular repair in this setting are limited to patients who are at too high risk for anesthesia, have a hostile groin, or would not survive significant bleeding. We report the case of a traumatic femoral arteriovenous fistula, causing severe venous insufficiency and arteriomegaly, in a 58-year-old male, with history of traumatic gunshot wound complicated by popliteal DVT. Surgical options for arteriovenous fistula include open and endovascular repair but this patient's fistula was more suitable for endovascular repair for reasons that will be discussed.